KELAYAKAN USAHA PETERNAKAN SAPI POTONG DI KABUPATEN WONOGIRI - , Bambang Sulistiono,SE, Dr. Ir. Suhatmini Hardyastuti. M,S ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Focus in yhis research is to known (1) Knowing feasibility of fatting cattle trade, (2) Knowing fatting cattle trading risk and (3) knowing something will be done to eliminate or minimizing risk that will be happen in the trade of fatting cattle. This research will be done about fatting cattle trade in Wonogiri district became the defrayal benefitted on support by soft loan to breeder among KKPE programs. The method using in this research is deskriptive analysis. Analysis method in this research using feasibility analysis, that is including soft loan term, B/C ratio, Ï, Ï/C ratio dan BEP. Final conclusion in this research is (1) Fatting cattle trade in Wonogiri district by KKPE programs feasible to be done, (2) Fatting cattle trade in Wonogiri district by sensitivity analysis given good contribute in financial effect, (3) Fatting cattle trade will be done if farmer group officer and breeder always use the technique from the agency and (4) To PT. BRI, if something happened to effect not be paymen on loan and taxes, could be effort to found the solution and will be done anything by the rules.